PELAKSANAAN PERATURAN KAPOLRI NOMOR 22 TAHUN 2010 TERHADAP FUNGSI DAN PERAN SENTRA PELAYANAN KEPOLISIAN TERPADU DI MASA PANDEMI COVID-19 (Studi Analisis Di Polsek Ratu Samban Kota Bengkulu) - Risuldi, Ujang (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract: The formulations how is the implementation of the functions and roles of the Integrated Police Service Center based on the Regulation of the Chief of Police of the Republic of Indonesia Number 22 of 2010 in the Ratu Samban Police Sector during the Covid-19 pandemic. Second, what factors affect the implementation of the function and role of the Integrated Police Service Center based on the Regulation of the Chief of the Indonesian National Police Number 22 of 2010 in providing services to the community during the Covid-19 pandemic. This type of research is juridical sociological. This study concludes: first, the integrated service center of the Ratu Samban Police Sector in accordance with the Regulation of the Chief of the Police of the Republic of Indonesia Number 22 of 2010 carries out functions, including coordinating and providing assistance and assistance, including handling the scene of the case including the first action at the scene of the case and processing crime scene, road management and traffic control, telephone service, short message, facsimile, internet (social networking), and mail. Presentation of general information related to the public interest in accordance with the provisions of the legislation. The types of services provided are handling of crime scenes, road management and traffic control and administrative services. Second, the integrated service center of the Ratu Samban Police acts as: first, a supporting law enforcement instrument to prevent the spread of disease and an instrument for public education. Third, the factors that influence the implementation of the function and role of the integrated police service center of the Ratu Samban Police are the first factors supporting facilities such as buildings, cleanliness, tidiness and comfort of space, polite and attractive officers, spacious parking lots. Inhibiting factors consist of limited number of personnel and lack of work facilities. Keywords : Regulation of the Chief of Police of the Republic of Indonesia Number 22 of 2010, Roles and Functions Abstrak: Rumusan masalah bagaimana pelaksanaan fungsi dan peran Sentra Pelayanan Kepolisian Terpadu berdasarkan Peraturan Kepala Kepolisian Republik Indonesia Nomor 22 Tahun 2010 di Kepolisian Sektor Ratu Samban di masa pandemi Covid -19. Kedua, faktor apa saja yang mempengaruhi pelaksanaan fungsi dan peran Sentra Pelayanan Kepolisian Terpadu berdasarkan Peraturan Kepala Kepolisian Republik Indonesia Nomor 22 Tahun 2010 dalam memberikan pelayanan kepada masyarakat di masa pandemi Covid-19. Jenis penelitian ini adalah yuridis sosiologis. Penelitian ini menyimpulkan : pertama, sentra pelayanan terpadu Kepolisian Sektor Ratu Samban sesuai dengan Peraturan Kepala Kepolisian Republik Indonesia Nomor 22 tahun 2010 menjalankan fungsi antara lain pengkoordinasian dan pemberian bantuan serta pertolongan, antara lain penanganan tempat kejadian perkara meliputi tindakan pertama di tempat kejadian perkara dan pengolahan tempat kejadian perkara, pengaturan jalan dan pengawalan lalulintas, pelayanan melalui telepon, pesan singkat, faksimili, internet (jejaring sosial), dan surat. Penyajian informasi umum yang berkaitan dengan kepentingan masyarakat sesuai dengan ketentuan peraturan perundang-undangan. Jenis layanan yang diberikan di adalah penanganan tempat kejadian perkara, pengaturan jalan dan pengawalan lalulintas dan pelayanan administrasi. Kedua, sentra pelayanan terpadu Polsek Ratu Samban berperan sebagai : pertama, instrumen penegakan hukum pendukung mencegah penyebaran penyakit dan instrument edukasi masyarakat. Ketiga, faktor yang mempengaruhi pelaksanaan fungsi dan peran sentra pelayanan kepolisian terpadu Polsek Ratu Samban adalah pertama faktor pendukung fasilitas seperti gedung, kebersihan, kerapihan dan kenyamanan ruang, Aparat sopan dan menarik, tempat parkir luas. Faktor penghambat terdiri dari keterbatasan jumlah personil dan kekurangan fasilitas kerja. Kata kunci : Peraturan Kepala Kepolisian Republik Indonesia Nomor 22 Tahun 2010, Peran dan Fungsi